THE ROLE OF ICE-BREAKING ACTIVITIES IN SUPPORTING STUDENTS’ LEARNING MOTIVATION IN INDONESIAN LANGUAGE LEARNING AT AN ELEMENTARY SCHOOL - Asril Kisbat Sitepu Sitepu; Ateta Malem Br. Sinulingga Sinulingga; Meikardo Samuel Prayuda; Maria Sihotang (Jurnal Pendidikan: Media, Strategi, dan Metode, 2025)
Learning motivation is an essential factor that influences students’ participation, attention, and emotional involvement in classroom activities, especially at the elementary school level. However, monotonous teaching practices may cause students to feel bored, passive, and less interested in learning Indonesian language subjects. This study aims to analyze the role of ice-breaking activities in supporting students’ learning motivation in Indonesian language learning among fourth-grade students at SD Negeri 064024 Medan. This research employed a qualitative descriptive method. The data were collected through classroom observation and semi-structured interviews with five fourth-grade students. The findings show that ice-breaking activities helped create a more enjoyable, active, and emotionally supportive classroom atmosphere. Students expressed that-games, singing, quizzes, and short interactive activities made them feel more enthusiastic and reduced boredom during the learning process. The observation also indicated that students showed more positive responses when the learning process included ice-breaking activities compared to regular instruction without such activities. The study concludes that ice-breaking activities can function as a practical instructional strategy to support students’ motivation, improve classroom engagement, and reduce learning fatigue in Indonesian language learning. Therefore, teachers are encouraged to integrate simple and meaningful ice-breaking activities into classroom instruction to maintain students’ attention and enthusiasm.